2020
DOI: 10.3390/antibiotics9110791
|View full text |Cite
|
Sign up to set email alerts
|

Development of Resistance in Escherichia coli ATCC25922 under Exposure of Sub-Inhibitory Concentration of Olaquindox

Abstract: Quinoxaline1,4-di-N-oxides (QdNOs) are a class of important antibacterial drugs of veterinary use, of which the drug resistance mechanism has not yet been clearly explained. This study investigated the molecular mechanism of development of resistance in Escherichia coli (E. coli) under the pressure of sub-inhibitory concentration (sub-MIC) of olaquindox (OLA), a representative QdNOs drug. In vitro challenge of E. coli with 1/100× MIC to 1/2× MIC of OLA showed that the bacteria needed a longer time to develop r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
(76 reference statements)
1
13
1
Order By: Relevance
“…Another research showed that purL or purM mutant disrupted purine biosynthesis in Burkholderia [47] . It was also demonstrated that purA gene was up-regulated in olaquindox resistance E. coli [24] . Previous study showed that KEGG pathway of purine metabolism, pyrimidine metabolism was enriched in the proteomics analysis of…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another research showed that purL or purM mutant disrupted purine biosynthesis in Burkholderia [47] . It was also demonstrated that purA gene was up-regulated in olaquindox resistance E. coli [24] . Previous study showed that KEGG pathway of purine metabolism, pyrimidine metabolism was enriched in the proteomics analysis of…”
Section: Discussionmentioning
confidence: 92%
“…To select de novo generated mutants, S. Enteritidis CICC21527 was cultured and passaged respectively in LB medium containing ENR at concentrations lower than MIC values, including 0.031 μg/mL (1/2×MIC), 0.016 μg/mL (1/4×MIC), 0.008 μg/mL (1/8×MIC), 0.004 μg/mL (1/16×MIC), 0.002 μg/mL (1/32×MIC), 0.001 μg/mL (1/64×MIC) and 0.0005 μg/mL (1/128×MIC). The culturing, passaging and mutant screening methods were carried as previously described [23,24] . The MICs of the selected mutants were confirmed by antimicrobial susceptibility testing.…”
Section: In Vitro Selection Of Mutants Under Sub-mics Of Enrmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research showed that purL or purM mutant disrupted purine biosynthesis in Burkholderia [38]. It was also demonstrated that purA gene was up-regulated in olaquindox resistance Escherichia coli (E. coli) [39]. Previous study showed that KEGG pathway of purine metabolism, pyrimidine metabolism was enriched in the proteomics analysis of FQs resistance E. coli [40].…”
Section: Discussionmentioning
confidence: 99%
“…When glutathione was added during the antimicrobial challenge, the H 2 O 2 tolerance of the BW25113-∆wrbA biofilms increased. Significant upregulation of WrbA was observed in Salmonella enterica serovar Enteritidis ATCC 4931 biofilms exposed to benzalkonium chloride [100] and in resistant E. coli cells challenged with sub-lethal concentrations of olaquindox [101]. The gene wrbA was upregulated in persister cells, suggesting the contribution of the WrbA in antimicrobial defense mech-anisms [102][103][104].…”
Section: Wrba Affects the Biofilm Tolerance To H 2 O 2 But Not To 2-chlorobenzoic Acidmentioning
confidence: 99%